Can the Reverse Mixed Reform Improve the Level of Risk-Taking by Private Enterprises? - Chen, Xiaofang; Chen, Yinge; Chen, Xin; Wang, Zhitao (Transformations In Business & Economics, 2024)
As market risks and market competition continue to intensify, how to improve the risk-taking level of enterprises has attracted extensive attention from the academic community. To explore the relationship between reverse mixed reform and the risk-taking level of private enterprises, using a sample of Chinese A-share listed companies in Shanghai and Shenzhen from 2007 to 2022, and drawing on the signaling and principal–agent theories, the impact of reverse mixed reform of private enterprises on their level of risk-taking level was examined from two aspects of equity structure and high-level governance. Results show that reverse mixed reform significantly improves the level of private enterprise risk-taking, and it is more obvious at the high-level governance level. In terms of equity structure, reverse mixed reform improves the level of private enterprise risk-taking by alleviating credit discrimination. Meanwhile, high-level governance provides further evidence of the intermediary effect of agency costs. Private firm engagement in reverse mixed reform is moderated by factors such as industry competition and management power. Conclusions are useful additions to the study of the economic effects of mixed ownership reform and have a high policy reference value on how to stimulate the vitality of market players and better utilize the advantages of the integration of state-owned capital and private capital.